ATTITUDES OF LITHUANIAN CONSUMERS TOWARDS THE COUNTRY OF ORIGIN OF WINE - Časas, Ramūnas; Makauskienė, Birutė (Ekonomika, 2013)
Abstract. The purpose of the study was to evaluate the attitudes of Lithuanian consumers towards the country of origin (COO) of wine. The main factors that influence the effect of COO and the mechanism of its formation were identified. The effects of social stereotypes, described by a Stereotype Content Model, on consumers’ attitudes are also analyzed, identifying the competence and warmth of the COO as important antecedents of consumers’ attitudes. The region of the origin of wine (appellation, protected designation of origin – PDO) have been identified as another important place-of-origin cue determining the consumer’s choice. A quantitative empirical research method – online survey – was used for the purpose of the study. The results have revealed that there are three types of wine consumers’ involvement: cognitive involvement, emotional product involvement, and emotional situational involvement, and that the importance of wine’s COO and region of origin (appellation, PDO) for consumers differs depending on the type and level of a consumer’s involvement. The existence of a statistically significant correlation among consumers’ attitude towards the COO of wine and the country’s competence and warmth has been proven, together with a possible relation between the type of a consumer’s involvement (cognitive, emotional situational or emotional product involvement) and the influence of COO competence and warmth on consumers’ attitude towards a wine. The research has also revealed an important positive relationship among consumer identification with the COO of wine, evaluation of COO competence, and the warmth and consumer attitude towards the COO of wine. Key words: country of origin of wine, consumers’ attitude, consumers’ involvement, stereotype content model stify;">